The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/polym12030675
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization, Structures, and Properties of Different Polyolefins with Similar Grafting Degree of Maleic Anhydride

Abstract: Maleic anhydride (MAH) grafting to different polyolefins with similar grafting degree can have different effects on crystallization, crystal structure, and mechanical and thermal properties. The grafting leads to a smaller crystal size, less ordered lamellar structure, and a shorter long period for HDPE, LLDPE, and PP. The grafting makes PP lamellar packing less ordered the most and almost no effect to LLDPE. The grafting does not have that much impact on the crystallization ability of the HDPE, LLDPE, and HDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…It can be observed that PP-gAPP shows higher modulus and tensile strength than PP and PP-gMA. This could be attributed to the significant decrease in molecular weight and increase in melt index when MAH is grafted into PP as was reported elsewhere 41 and to the more rigid structure of APP. It also can be seen that the composite samples compatibilized with PP-gAPP show better mechanical properties with higher modulus and tensile strength.…”
Section: Mechanical Propertiessupporting
confidence: 66%
“…It can be observed that PP-gAPP shows higher modulus and tensile strength than PP and PP-gMA. This could be attributed to the significant decrease in molecular weight and increase in melt index when MAH is grafted into PP as was reported elsewhere 41 and to the more rigid structure of APP. It also can be seen that the composite samples compatibilized with PP-gAPP show better mechanical properties with higher modulus and tensile strength.…”
Section: Mechanical Propertiessupporting
confidence: 66%
“…XRD measurements were conducted to study the structure of the RHDPE, WGP and MAgPE raw materials in addition to the RHDPE/MAgPE/WGP composite at the optimum mixture (78.5 wt.% RHDPE,1.5 wt.% MAgPE and 20 wt.% WGP) before and after the thermal milling consolidation process, as shown in Figure 7 (d) . As shown, the two characteristic diffraction peaks of HDPE at 2 θ = 21.4° and 23.9° corresponding to the 110 and 200 orthorhombic crystalline planes [ 33 ], respectively, were observed in RHDPE, suggesting that the crystal structure of RHDPE remained unchanged after cold milling. Similarly, the amorphous structure of WGP and semicrystalline structure of MAgPE were not affected by milling.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, as extensively reported in the literature for virgin polyethylene/polypropylene blends [ 19 , 20 ] and, as also successfully implemented by means of the reactive extrusion of Fil-s [ 6 ], the maleic anhydride is able to stabilize the macro-radicals’ sites formed during the reaction of the polymer with a peroxide. In other words, it creates an inter-chain block or graft copolymers, leading to enhanced compatibility and improved mechanical properties [ 21 ] of the obtained material.…”
Section: Resultsmentioning
confidence: 99%
“…The alternative strategy for Fil-s upgrading, which foresees the addition of a PE/PP-g-MA compatibilizer, instead of the direct, reactive grafting/compatibilization with maleic anhydride of the recycled material, offers the twofold advantage of providing the plastics converters with a ready-to-use compatibilizer and of more easily tuning the compatibilization process. Concerning this latter issue, while it is well known that the inherent complexity of conducting free radical reactions for grafting MA on virgin polyolefin matrices, without extensive side reactions [ 20 , 21 ], many further difficulties arise when the material comes from the post-consumer polymeric waste stream, due to the unpredictable presence of several types of contaminants [ 6 ], which might affect the yield and effectiveness of the reaction.…”
Section: Resultsmentioning
confidence: 99%